2009
DOI: 10.1111/j.1365-3164.2009.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal colonization of mucosal and lesional skin sites in atopic and healthy dogs

Abstract: Staphylococcal colonization was compared in healthy dogs and in dogs with atopic dermatitis. Bacterial swabs were collected from the nasal mucosa, ear and perineum of 43 healthy and 24 atopic dogs and also from potentially infected skin lesions of the atopic dogs. Coagulase positive staphylococcal isolates were identified to the species level. At the time of this study Staphylococcus intermedius was considered a single species but has since been recognized as comprising at least three species with canine isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 33 publications
7
91
1
3
Order By: Relevance
“…All swabs were transported to our laboratory, following placement in Stuart's transport medium (Becton, Dickinson and Co.). The methods to identify CoPS isolates were performed as previously described [10,14] with partially modification. Swabs were inoculated by streaking onto mannitol salt agar plates (Nissui Pharmaceutical Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…All swabs were transported to our laboratory, following placement in Stuart's transport medium (Becton, Dickinson and Co.). The methods to identify CoPS isolates were performed as previously described [10,14] with partially modification. Swabs were inoculated by streaking onto mannitol salt agar plates (Nissui Pharmaceutical Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Five dogs (55.6%) in which this bacterium was isolated had dermatitis, other carriers had respiratory and digestive diseases. Fazakerley et al (2009) found that 87.5% dogs with atopic dermatitis were colonized with S.(pseud)intermedius compared to 37.2% of healthy dogs in a UK performed research.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have considered anatomic site patterns of S. pseudintermedius carriage in dogs (Harvey and Noble, 1998;Hartmann et al, 2005;Griffeth et al, 2008;Rubin and Chirino-Trejo, 2011;Paul et al, 2012) and cats (Abraham et al, 2007). However, fewer studies that detail canine and especially feline anatomic carriage site patterns of S. aureus are available (Abraham et al, 2007;Griffeth et al, 2008;Fazakerley et al, 2009;Davis et al, 2014). The primary aim of this study was to systematically test the sensitivity of different anatomic sites for the recovery of S. aureus and MRSA among companion animals living in the home of a person recently treated for MRSA skin or soft tissue infection (SSTI).…”
Section: Introductionmentioning
confidence: 99%